Changes in Body Weight, Serum (Sodium, Potassium) and Serum Albumin after Intermaxillary Fixation in Traumatized and Obese Patients (Comparative Study) - Wael Sheet; Mohmmed K. Hassouni (University of Mosul, College of Dentistry, 2012)
Aims of the study: to evaluate the effects of intermaxillary fixation (IMF) on body weight, serum electrolytes ( Na+ and K+ ) and serum Albumin in traumatized and obese patients and to compare the changes between these two groups. Materials and Methods: A non randomized prospective study was done. The anthropometric measurement included 4 sites of skin fold thickness (triceps, biceps, subsca-pular and suprailiac skin folds), upper arm circumference, body mass index and laboratory investiga-tions to assess serum(Na+ and K+) levels and serum albumin level. The patients were divided in to 2 groups, the first group included 25 traumatized patients and the second group included 7 volunteer ob-ese patients and IMF was placed for those patients as one of the treatment lines for their body weight reduction and were considered as the control group. The parameters were recorded for each patient in the 2 groups preoperatively, one week, three weeks and six weeks postoperatively. Paired and un paired T tests were used in the statistical analysis, a P value < 0.05 was considered highly significant. Results: The changes of the anthropometric measurements, body mass index, serum K+ and serum albumin were statistically highly significant in traumatized patients with body weight loss ranging be-tween (5-8) Kg in this group. The changes of the anthropometric measurements and body mass index in the obese patients group were also statistically highly significant with a loss of (5-6) Kg in body weight in this group. The changes of anthropometric measurements and body mass index were statisti-cally highly significant in traumatized patients than in obese patients, while the changes in serum (Na+ and K+ ) and serum Albumin level were statistically not significant between the two groups. Conclu-sion: IMF compromises the nutritional status of the patients leading to loss of water, fat and protein in both traumatized and obese patients but the effect more pronounced in traumatized patient due to the metabolic and hormonal response to trauma together with the limited oral intake.